Investigation of RBC Indices and HbA2 Levels in Parents of Beta-Thalassemia Patients: Impacts on Premarital Genetic Counseling - Mina Izadyar; Jila Dastan; Tayebeh Sabokbar; Solmaz Shoraka; Azadeh Shojaei; Habib Nasiri; Saeed Reza Ghaffari (Tehran University of Medical Sciences, 2007)
Objective: This study was designed to investigate RBC indices and HbA2 levels in parents of major beta-thalassemia patients to detect possible silent beta- thalassemia carriers and examine its potential impact on the premarital genetic counseling. Materials and Methods: This cross sectional study was performed at Children Medical Center from 2004 to 2006. After genetic counseling and getting informed consent, peripheral blood sampling was carried out on 185 carrier parents of regularly blood transfused thalassemia children. Then RBC indices and HbA2 concentration were measured. Samples with MCV and MCH higher than and/or HbA2 lower than cut off values were rechecked. Results: In one case, MCV and MCH indices were within the limits defined for non beta- thalassemia carriers. Furthermore, four other cases were found to have decreased values of MCV and MCH but normal HbA2 levels. Conclusion: About 3% of beta-thalassemia carriers in our country may potentially be missed using current screening methods. Further studies are required to assess the need for presenting a new threshold for thalassemia carrier screening. Defining the causative mutations using molecular methods would pave the way for establishing a protocol for a premarital screening program in conditions when one of couples is a confirmed carrier.